Using Population Descriptors in Genetics and Genomics Research: A New Framework for an Evolving Field - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Genetic and genomic information has become far more accessible, and research using human genetic data has grown exponentially over the past decade. Genetics and genomics research is now being conducted by a wide range of investigators across disciplines, who often use population descriptors inconsistently and\/or inappropriately to capture the complex patterns of continuous human genetic variation. In response to a request from the National Institutes of Health, the National Academies assembled an interdisciplinary committee of expert volunteers to conduct a study to review and assess existing methodologies, benefits, and challenges in using race, ethnicity, ancestry, and other population descriptors in genomics research. The resulting report focuses on understanding the current use of population descriptors in genomics research, examining best practices for researchers, and identifying processes for adopting best practices within the biomedical and scientific communities.

The Genomic Revolution: Unveiling the Unity of Life - Michael Yudell; Robert DeSalle (The National Academies Press, 2002)

Direct-to-Consumer Genetic Testing: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Today, scores of companies, primarily in the United States and Europe, are offering whole genome scanning services directly to the public. The proliferation of these companies and the services they offer demonstrate a public appetite for this information and where the future of genetics may be headed; they also demonstrate the need for serious discussion about the regulatory environment, patient privacy, and other policy implications of direct-to-consumer (DTC) genetic testing. Rapid advances in genetic research already have begun to transform clinical practice and our understanding of disease progression. Existing research has revealed a genetic basis or component for numerous diseases, including Parkinson's disease, Alzheimer's disease, diabetes, heart disease, and several forms of cancer. The availability of the human genome sequence and the HapMap, plummeting costs of high-throughput screening, and increasingly sophisticated computational analyses have led to an explosion of discoveries of linkages between patterns of genetic variation and disease susceptibility. While this research is by no means a straight path toward better public health, improved knowledge of the genetic linkages has the potential to change fundamentally the way health professionals and public health practitioners approach the prevention and treatment of disease. Realizing this potential will require greater sophistication in the interpretation of genetic tests, new training for physicians and other diagnosticians, and new approaches to communicating findings to the public. As this rapidly growing field matures, all of these questions require attention from a variety of perspectives. To discuss some of the foregoing issues, several units of the National Academies held a workshop on August 31 and September 1, 2009, to bring together a still-developing community of professionals from a variety of relevant disciplines, to educate the public and policy-makers about this emerging field, and to identify issues for future study. The meeting featured several invited presentations and discussions on the many technical, legal, policy, and ethical questions that such DTC testing raises, including: (1) overview of the current state of knowledge and the future research trajectory; (2) shared genes and emerging issues in privacy; (3) the regulatory framework; and (4) education of the public and the medical community.

Human Genome Editing: Science, Ethics, and Governance - National Academy of Sciences; National Academy of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Genome editing is a powerful new tool for making precise alterations to an organism's genetic material. Recent scientific advances have made genome editing more efficient, precise, and flexible than ever before. These advances have spurred an explosion of interest from around the globe in the possible ways in which genome editing can improve human health. The speed at which these technologies are being developed and applied has led many policymakers and stakeholders to express concern about whether appropriate systems are in place to govern these technologies and how and when the public should be engaged in these decisions. Human Genome Editing considers important questions about the human application of genome editing including: balancing potential benefits with unintended risks, governing the use of genome editing, incorporating societal values into clinical applications and policy decisions, and respecting the inevitable differences across nations and cultures that will shape how and whether to use these new technologies. This report proposes criteria for heritable germline editing, provides conclusions on the crucial need for public education and engagement, and presents 7 general principles for the governance of human genome editing.